Progress of Land Reform - Planning Commission (Planning Commission, 1960)
The proposals for land reform in the Second Five Year Plan: related to : abolition of intermediaries ; tenancy reforms i.e. regulation of rent, security of tenure for tenants and conferment of ownership on them ; ceiling on land holdings ; and agrarian reorganisation, including consolidation of holdings; and prevention of sub-division and fragmentation. These proposals are set out in a summary form in annexure I. A. brief review of the progress made in the implementation of these proposals is set out in the following paragraphs.
Government of India Planning Commission
Government of India Planning Commission